Hybrid Long-Period Fiber Grating with Multimode Fiber Core for Refractive Index Measurement - 邵敏 乔学光 任学良 杨德兴 (中国物理快报：英文版, 2017)
A refractive index(RI) sensor based on hybrid long-period fiber grating(LPFG) with multimode fiber core(MMFC) is proposed and demonstrated. The surrounding RI can be determined by monitoring the separation between the resonant wavelengths of the LPFG and MMFC since the resonant wavelengths of the LPFC and MMFC will shift in opposite directions when the surrounding RI changes. Fxperimental results show that the sensor possesses an enhanced sensitivity of 526.92 nm/RIU in the RI range of 1.387-1.394 RIU. The response to the temperature is also discussed.